The Legacy of Colonial Land Law and Implications for Compensation in Communal Land Areas of Zimbabwe - Chavunduka, Charles; Mukwambo, James Lomax (Journal of Law, Society and Development, 2025)
Globally and in developing countries in particular, rural communities living on communal land face the risk of displacement by development projects such as those related to mineral exploration and mining. In many cases, displaced communities have not been adequately compensated. The article investigates how legacies of colonial land laws have continued to impact the rights of communal people. A qualitative approach that is based on a case study design is used to explore the research objective. Data collection used a desktop review, complemented by case law and newspaper reports, and the data was subjected to thematic analysis. The results show that although the 2013 Constitution of Zimbabwe expanded the buddle of rights to land for communal people, the relevant provisions of the supreme law are yet to be operationalised. Innovations on compensation that are based on new approaches by international agencies have received more uptake by the private sector rather than the government. The way forward calls for the implementation of relevant provisions of the Constitution and the reform of land-related laws and institutions.